Stable posture control for planar hyper-redundant arms using selective control points. (17th December 2017) - Dione, Aime Charles Alfred; Hasegawa, Shoichi; Mitake, Hironori
Abstract: The high degree of freedom in hyper-redundant arms makes resolving their redundancy using Jacobian techniques impractical. Furthermore, Jacobian techniques are adapted for the specification of tasks focused around the end-effector, they are not well equipped to capture tasks where arm posture control is preponderant like locomotion or manipulation. For these type of arms, parameterized modal curve based approaches are often deemed superior. However, these curves restrict the arms to a predefined type of postures and adding extra mode functions to account for more complex postures makes solving the inverse kinematics more challenging. This paper explores a method to reliably achieve posture tracking for hyper-redundant planar arms using the more simple Jacobian formulation. The introduced method attempts to track arbitrary target postures. This method is characterized by the ability for the arm to depart from, traverse or land on singular postures. Abstract :